Vegetarian Diet During Pregnancy: Assessment and Support. Issue 5 (September 2017) - Snow, Denise
Abstract : Vegetarian and vegan diets can be safe during pregnancy and are becoming more popular among pregnant women. Knowledgeable and non-judgmental nursing support is essential for effective perinatal nutritional counseling. Welcome to our new nutrition columnist, Denise Snow, a clinical associate professor in the School of Nursing at the State University of New York at Stonybrook and a healthcare law attorney in a private practice.